Construction of a secure storage and sharing model for medical data under computer network technology - Yin, Peng; Yin, Ting; Zhao, Sijia; Yu, Shan (Applied mathematics and nonlinear sciences, 2024)
This paper constructs a secure storage and sharing model of medical data based on the blockchain technology of computer network technology, and the model mainly designs the encryption process, storage process and sharing process of medical data. The model combines asymmetric encryption algorithm and ciphertext access strategy and designs a hybrid encryption method for secure storage and sharing of medical data through three stages: public parameters and key generation, encryption and decryption. The comprehensive performance of the constructed model is tested, and the security performance indexes are 0.998, 0.989, 0.996 and 0.993 and the execution time of the sharing mechanism is 1~16s, the data upload time is 1200ms, and the data download time is only 200ms.